Recursive and adaptive processes in strategic work: municipality leaders' and school leaders' accounts of their work for educational reform - Ruth Jensen; Emerita Eli Ottesen (Taylor & Francis Group, 2023)
ABSTRACTThe purpose of this study is to contribute insights into strategic work in an educational reform context. Empirical data were collected from four cases in Norway, where the national educational authority recently initiated a renewal of the national curriculum for primary and secondary education. The theory of strategy as practice was the analytical framework applied in this study. The aims were to investigate municipal and school leaders' accounts of strategic work and the relationships between strategic work at the municipal and school levels. The informants experienced they had leeway to decide on how to realize the national reform in their local contexts. In their processes of strategic work, they included both well-known strategies and practices that had worked previously and structures and procedures that were adapted to the situation at hand. We found a smooth alignment between recursive and adaptive processes across the organizational levels. The informants implemented their perceptions as the intention of the national reform in many ways. In demonstrating the complexity of educational reform work, the findings of this study showed that the SaP approach may be used to make valuable theoretical contributions to our understanding of reform work in education.